Adoption of digital fisheries monitoring system in Timor-Leste enables science driven development prioritisation - CGIAR Platform for Big Data in Agriculture (2019)
The digital pipeline and script to automate fisheries analytics has led to Timor-Leste government uptake and utilization of the system to manage fisheries and prioritize fisheries development and extension support to fishers and fish workers.